The Innovation Paradigm of New Industrialization in the Conditions of the Integrated World Economic Way - Romanova, Olga Aleksandrovna (Economy of Regions, 2017)
The article emphasizes the importance of the concept of «technical and economic paradigm», which characterizes the certain stage of the world economy development associated with the corresponding technological revolution. The paper reveals the feature of the modern technical and economic paradigm development connected with new concepts determining a priority of general values. The author states the hypothesis that in the conditions of the emergence of the fourth industrial revolution elements (so-called 4.0 industry), it is fair to consider the innovation paradigm of development as the foundation of the new industrialization which preceds this revolution. The author considers new industrialization as the process contributing to the global technological parity of Russia and the countries-technological leaders. The most significant statements from this post of view are allocated: consideration of new industrialization as a process of continuous innovations and distribution of breakthrough technologies, computerization of production, robotization, cross-disciplinary nature of high technologies, the ecology of technologies, intellectualization of the potential of all persons occupied in industrial production, etc. The author analyses strategic documents connected with the development of innovative activities in Russia. The paper emphasizes that the indicators characterizing these activities do not allow to rank Russia as a country having the developed innovative economy. The article reveals the possibilities of the activation of innovative activities in Russia connected to the development of the approved private priorities in the main spheres of activity with the state priorities of social development; with construction of integrated strategy of a scientific and technological, institutional and industrial development of the country; with creation of the system of scientific monitoring allowing to adjust the necessary corrective actions in time. The article emphasizes a dominant nature of the institutional environment predetermining a success of socio-economic and innovative development of national economy. New integrated world economic way is forming in the conditions of the increasing importance of an innovation paradigm. The successfulness of its implementation is determined by a ratio of the inclusive (involving) and extractive (taking out) economic and political institutes.